1994
DOI: 10.1002/jmri.1880040114
|View full text |Cite
|
Sign up to set email alerts
|

Tissue temperature monitoring for thermal interventional therapy: Comparison of T1‐weighted MR sequences

Abstract: For thermal interventional therapy, near real-time monitoring of temperature changes in the treated area is desirable. In this study, various fast T1-weighted magnetic resonance (MR) imaging protocols were compared to determine the sensitivity and resolution of signal intensity for temperatures within the range of 36 degrees C-66 degrees C in gel phantoms and in vitro porcine liver specimens. The results showed that a T1-weighted fast spin-echo sequence with a TR of 100 msec had better temperature sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 9 publications
3
54
0
Order By: Relevance
“…The days following ILT, in all imaging studies we found a low signal intensity zone on dynamic T1-weighted sequences, hyperintense on T2-weighted images, that (as previous experiments and studies have shown in 13,17,21,30,36) corresponded to tissue necrosis within the tumor ( Figure 6). …”
Section: Optical Flow Computation and Displaysupporting
confidence: 84%
See 3 more Smart Citations
“…The days following ILT, in all imaging studies we found a low signal intensity zone on dynamic T1-weighted sequences, hyperintense on T2-weighted images, that (as previous experiments and studies have shown in 13,17,21,30,36) corresponded to tissue necrosis within the tumor ( Figure 6). …”
Section: Optical Flow Computation and Displaysupporting
confidence: 84%
“…Diffusion sequences [4][5][6]13] have a relatively high sensitivity ad therefore may be used for temperature mapping. But the enhanced temperature sensitivity in diffusion imaging comes at the expense of a low signal-to-noise ratio in the images an requires fast or ultrafast imaging methods to avoid the effect of macroscopic motion.…”
Section: Comparison Of Image Sequences and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The signal decreases with increasing temperature both because the relaxation time increases and the magnetization decreases. The small nonlinear temperature dependence on the equilibrium magnetization is often neglected (26) or, alternatively, Eq. [7] is modified to (27):…”
Section: T 1 Relaxation Time Of Water Protonsmentioning
confidence: 99%